REVITALISASI BAHASA DAERAH HAMPIR PUNAH SEBAGAI DOKUMENTASI BAHASA - Ade Rahima (Pengabdian Deli Sumatera, 2024)
The aim of this service is to see a general picture of the condition of the vitality of regional languages ​​in Jambi Province. The method used in this service is Action Research. The status of the language from the results of this research study is the actions that need to be taken on the language concerned, whether it needs to be conserved, revitalized, or both conserved and revitalized. The conclusion of this service is that documenting languages ​​is actually the first step in efforts to revitalize languages ​​that are threatened with extinction.